LIVELIHOODS AND EMPOWERMENT: THE KUDUMBASHREE PROJECTS IN KERALA, INDIA : A NEW PARADIGM OF PARTICIPATORY ECONOMY - V\P RAGHAVAN
Poverty alleviation schemes based on micro- credit system have been implemented in many of the developing countries in recent years. The Government of Kerala State in India has introduced a novel scheme of poverty alleviation based on micro-credit and self help grouping. Paraphrased as Kudumbashree ( `Prosperity of the Family'), the scheme aims at improving the living levels of the poor women in rural and urban areas. It seeks to bring the poor women folks together to form the grass root organizations to help enhance their economic security. The project aimsat removing poverty among ruralwomen households through setting up of micro-credit and productive enterprises. The activities such as micro-credit and micro-enterprises under the scheme were undertakenby the locally formed Community Development Societies consisting of poor women. The State Poverty Eradication Mission-Kudumbashree- launched by the Government of Kerala in India is a massive poverty eradication programme in contemporary history. It has proved without doubt that women empowerment is the best strategy for poverty eradication. Women, who were regarded as voiceless and powerless started identifying their inner strength, opportunities for growth , and their role in reshaping their own destiny. The process of empowerment becomes the beacon light to their children, their families and the society at large. It opens a new vistas in development history. A new paradigm of participatory economics has been found emerging in "God's Own Country".Kudumbashree presents a unique model of participatory development , which can verywell , be emulated other developing countries